82.6k views
0 votes
Evaluate the expression.


-2+(–6)2×–2

1 Answer

0 votes

Answer:

-4 - 12x / -4×(1+3x)

Explanation:

-2+(-6)×2x-2

- multiplying an odd number of negative terms makes the product negative

(+(-6)= - ) -2-6×2x-2

- calculate the product

(6×2=12) - -2-12x-2

-calculate the difference

(-2-2=-4) - -4-12x

SOLUTION: -4-12x

/

-2+(-6)×2x-2

- calculate the difference

(-2-2) - -4+(-6)×2x

- factor out - 2×2 from the expression = -2×2(1+3x)

-multiply the numbers

(2×2=4) - -4×(1+3x)

SOLUTION: -4×(1+3x)

*both solutions are correct but i wasnt sure, which method you would rather use*

User Vic Goldfeld
by
5.0k points